Samuel Wilmot, Fish Culture, and Recreational Fisheries in late 19th century Ontario - Knight, William (Scientia Canadensis)

(untitled) (CSTHA/AHSTC, 2007)
AbstractHistorians have shown that fish culturists and anglers enjoyed a mutually beneficial relationship in 19th century North America. Sharing interests in producing and protecting fish for recreation, the two groups supported emerging regimes of fisheries administration and fish culture that privileged angling and game fish species. In Ontario, it has been argued that anglers achieved control of inland fisheries with help from state fish culturist Samuel Wilmot who, as a sportsman, shared anglers' recreational perspective. A closer look at Wilmot and fish culture in late 19th century Ontario, however, reveals a more complex struggle over recreational fisheries administration. I show that game fish culture under Wilmot was subordinated to fish culture programs that supported the Great Lakes commercial fisheries. Indeed, Wilmot resisted anglers' refraining of Ontario's fisheries as a private recreational resource. By the 1890s, however, this position was unpopular with Ontario's anglers and government officials, who demanded greater provincial control over recreational fisheries and fish culture. It was only after Wilmot's retirement in 1895 that game fish culture received higher priority in Ontario with both federal and provincial governments engaging in programs of wild bass transfers. In 1899, Ontario won a share of fisheries jurisdiction and established its first provincial fisheries administration, which laid the basis for more comprehensive programs of game fish culture in the 20th century.